Symbolic Interaction In Village Development - Muhammad Luthfie Supandi; Mohd Nor Shahizan Ali; Hudi Santoso (LPPM Universitas PGRI Sumatera Barat, 2025)
The problem of the research is about the efforts of the Muhammadiyah community organization that experienced obstacles in participating in village development in the Plompong area, Brebes, Central Java. The obstacles occurred, among others, due to differences with the village community, namely in the matter of religious worship beliefs. The purpose of the research is to analyze Muhammadiyah's efforts to participate in village development which began with symbolic interaction. The theory used to analyze the main problem of the research is Blumer's theory of symbolic interaction and Portes' theory of development. The research method uses a qualitative approach that is oriented towards descriptive explanations of the objects being studied. The collection of research materials was carried out using observation techniques, in-depth interviews, FGDs, and document studies. While the validity of the research data was carried out through triangulation techniques. The results of the study show that symbolic interaction carried out through interpersonal, dialogical and group communication can realize harmony and can pave the way for community empowerment. The conclusion shows that symbolic interaction is very important at the beginning of participation in village development. Novelty, produces a village development model in which there is symbolic interaction in the process.